A rare case of sudden death due to IgG4‐related giant coronary artery aneurysms. Issue 1 (2nd August 2021) - Chan, Shijia
Abstract: Immunoglobulin G4‐related disease (IgG4‐RD) is a fibro‐inflammatory condition that can affect many organs, either simultaneously or metachronously. In recent years, IgG4‐related vascular complications of larger arteries such as the aorta and iliac arteries have been increasingly identified. Among vascular complications, coronary artery involvement in the forms of either periarteritis or coronary artery aneurysms (CAAs) has also been reported; however, are very rare in comparison. This case report presents a rare case of a sudden death due to occlusive thrombosis of IgG4‐related giant CAAs measuring up to 10 cm in diameter, demonstrates their possible clinical progression, and shows how they can distort normal anatomy which may then pose challenges in the interpretation of postmortem‐computed tomography scans. It also briefly discusses the diagnosis of IgG4‐RD in arteries, both clinically and in the postmortem setting.